An analytical solution for the correct determination of crack lengths via cantilever stiffness. (September 2020) - Alfreider, Markus; Kolitsch, Stefan; Wurster, Stefan; Kiener, Daniel
Abstract: The present work provides an analytic solution for the stiffness to crack length relation in microscopic cantilever shaped fracture specimens based on classical beam theory and substitution of the crack by a virtual rotational spring element. The resulting compact relationship allows for accounting of the actual beam geometry and agrees very well with accompanying finite element simulations. Compared with the only other model present in literature the proposed relationship reduces the deviation between model and data to a maximum of 1.6% from the previous minimum of 15%. Thus, the novel solution will help to reduce the necessity for individual simulations and aim to increase the comparability of elastic-plastic microcantilever fracture experiments in the future.